A review of the fleas (Insecta: Siphonaptera) from Argentina - Lareschi, Marcela; Sanchez, Juliana; Autino, Analía (Zootaxa, 2016)
The Order Siphonaptera comprises cosmopolitan haematophagous ectoparasites of birds and mammals. More than ten years have past since the last list of species known for Argentina. Herein we provide a review of the fleas from the country, which includes an updated list, host species and geographical distribution for each taxa, as well as some comments. We report 127 species and subspecies belonging to eleven different families; 42 of these species are endemic. Four genera (Adoratopsylla, Cleopsylla, Ctenidiosomus, and Nonnapsylla) and six species and subspecies (Adoratopsylla (Adoratopsylla) antiquorum antiquorum, Agastopsylla pearsoni, Polygenis (Polygenis) roberti beebei, Plocopsylla (Plocopsylla) silewi, Plocopsylla (Plocopsylla) wilesi and Tunga terasma) are added to the list for Argentina. Nine species new to science are included, described on the bases of specimens collected from Argentina (Ctenidiosomus austrinus, Ectinorus (Ectinorus) lareschiae, Ectinorus (Ectinorus) spiculatus, Ectinorus (Ectinorus) morenoi, Hectopsylla narium, Plocopsylla (Plocopsylla) linardii, Neotyphloceras crackensis, Neotyphloceras pardinasii and Tunga perforans). Information provided herein contributes to the knowledge of the fleas from Argentina, necessary to a better understanding of their role as parasites themselves and vectors of zoonotic importance.